Cortical Dysplasia and Migraine: Is There Any Coincidental Association? - Kabakuş, Nimet; Kurt, Abdullah; Kurt, Ayşegül Neşe Çitak; Serhatlıoğlu, Selami (Fırat University, 2005)
Cerebral cortical malformations accompany epilepsy and refractory epilepsy, in particular. However, these malformations may also go together with other neurological, psychiatric and developmental disorders. The presentation of a case who has migraine aims to stress that if there is any coincidental association between cortical dysplasia and migraine, or migraine could be casued by cortical dysplasia. A 14-year-old male patient presented with weekly migrainous headaches that had been continuing for two years. Physical/neurological examination, level of intelligence, school performance, laboratory analyses and routine EEG were all normal. Headache period and sleep-deprived EEGs revealed anterior asymmetric slowing of background; no epileptiform activity. Cerebral magnetic resonance imaging of the case showed dysplastic area in the right frontal, digitation in inter-hemispheric sulcus anterior (cortical dysplasia). It was found that the case had been receiving β blocker treatment for 15 months, to which he responded (mild migraine attack bimonthly). Neuro-diagnostic examination of migraine patients for possible structural lesions might ensure making sense of conditions that can arise later, as well as treating surgically the lesions identified in cases resistant to medical treatment. ©2005, Fırat Üniversitesi, Tıp Fakültesi

Serebral kortikal malformasyonlar epilepsi, özellikle de dirençli epilepsi ile birliktelik gösterirler. Ayrıca bu bozukluklar diğer nörolojik, psikiyatrik ve gelişimsel bozukluklarla da birliktelik gösterebilir. Burada sunulan ve kortikal displazi ile migren birlikteliğini gösteren olgu, nöronal migrasyon bozukluklarının neden olabileceği başka klinik durumların da olabileceğini göstermekdir. On dört yaşında erkek hasta, iki yıldır devam eden, haftada bir kez olan migren özelliğinde baş ağrısı ile başvurdu. Fizik / nörolojik muayenesi / zeka düzeyi ile / rutin / baş ağrılı dönem ve uyku-yoksunluklu EEG'si normaldi. Olgunun beyin manyetik rezonans incelemesinde sağ frontal bölgede displazik alan, interhemisferik sulkus anteriorunda digitasyon (kortikal displazi) ile uyumlu görünüm vardı. Beş aydır β bloker tedavisi alan hastanın bu tedaviden yanıt aldığı (2 ayda bir hafif migren atağı)) belirlendi. Migrenli hastaların, olası yapısal lezyonlar yönünden daha detaylı nöro-diyagnostik yaklaşımlarla araştırılması, bu hastaların sonradan çıkabilecek olası klinikopatolojik durumların doğru değerlendirilmesine; ayrıca medikal tedaviye dirençli durumlarda belirlenen lezyon cerrahi tedavisine de olanak sağlayabilir. ©2005, Fırat Üniversitesi, Tıp Fakültesi
Kortikal Displazi ve Migren; rastlantısal bir birliktelik olabilir mi?